Complete mitochondrial genome sequence of the eastern gorilla (Gorilla beringei) and implications for African ape biogeography (2014)
ABSTRACT: The Western and Eastern species of gorillas (Gorilla gorilla and Gorilla beringei) began diverging in the mid-Pleistocene, but in a complex pattern with ongoing gene flow following their initial split. We sequenced the complete mitochondrial genomes of 1 Eastern and 1 Western gorilla to provide the most accurate date for their mitochondrial divergence, and to analyze patterns of nucleotide substitutions. The most recent common ancestor of these genomes existed about 1.9 million years ago, slightly more recent than that of chimpanzee and bonobo. We in turn use this date as a calibration to reanalyze sequences from the Eastern lowland and mountain gorilla subspecies to estimate their mitochondrial divergence at approximately 380 000 years ago. These dates help frame a hypothesis whereby populations became isolated nearly 2 million years ago with restricted maternal gene flow, followed by ongoing male migration until the recent past. This process of divergence with prolonged hybridization occurred against the backdrop of the African Pleistocene, characterized by intense fluctuations in temperature and aridity, while at the same time experiencing tectonic uplifting and consequent shifts in the drainage of major river systems. Interestingly, this same pattern of introgression following divergence and discrepancies between mitochondrial and nuclear loci is seen in fossil hominins from Eurasia, suggesting that such processes may be common in hominids and that living gorillas may provide a useful model for understanding isolation and migration in our extinct relatives.